A "Dirty" Footprint: Macroinvertebrate diversity in Amazonian Anthropic Soils. (10th July 2021) - Demetrio, Wilian C.; Conrado, Ana C.; Acioli, Agno N. S.; Ferreira, Alexandre C.; Bartz, Marie L. C.; James, Samuel W.; da Silva, Elodie; Maia, Lilianne S.; Martins, Gilvan C.; Macedo, Rodrigo S.; Stanton, David W. G.; Lavelle, Patrick; et al.
Abstract: Amazonian rainforests, once thought to be pristine wilderness, are increasingly known to have been widely inhabited, modified, and managed prior to European arrival, by human populations with diverse cultural backgrounds. Amazonian Dark Earths (ADEs) are fertile soils found throughout the Amazon Basin, created by pre‐Columbian societies with sedentary habits. Much is known about the chemistry of these soils, yet their zoology has been neglected. Hence, we characterized soil fertility, macroinvertebrate communities, and their activity at nine archeological sites in three Amazonian regions in ADEs and adjacent reference soils under native forest (young and old) and agricultural systems. We found 673 morphospecies and, despite similar richness in ADEs (385 spp.) and reference soils (399 spp.), we identified a tenacious pre‐Columbian footprint, with 49% of morphospecies found exclusively in ADEs. Termite and total macroinvertebrate abundance were higher in reference soils, while soil fertility and macroinvertebrate activity were higher in the ADEs, and associated with larger earthworm quantities and biomass. We show that ADE habitats have a unique pool of species, but that modern land use of ADEs decreases their populations, diversity, and contributions to soil functioning. These findings support the idea that humans created and sustained high‐fertility ecosystems that persist today, altering biodiversity patterns in Amazonia. Abstract : Amazonian Dark Earths (ADEs) are fertile soils found throughout the Amazon Basin, created by pre‐Columbian societies with sedentary habits. Much is known about the chemistry of these soils, yet their zoology has been neglected. Studying nine archeological sites in Amazonian regions and adjacent reference soils we found 673 morphospecies and, we identified a tenacious pre‐Columbian footprint, with 49% of morphospecies found exclusively in ADEs. These findings support the idea that humans created and sustained high‐fertility ecosystems that persist today, altering biodiversity patterns in Amazonia.